Um lugar de produção e a produção de um lugar: a história e a historiografia divulgadas no GT História da Educação da ANPEd (1985-2000) - Denice Barbara Catani; Luciano Filho Mendes de Faria (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
This text analyses the ground covered by the ANPEd Working Group on the History of Education (1985-2000) reconsidering the characteristics of the productions presented in the group and its constitutive process as a place of production for Brazilian historical educational research. It emphasises the role of the Working Group as a place for theoreticalmethodological discussions and for the nurturing of new research perspectives. It also identifies the emergence of theoretical perspectives and methodological options that have marked national production in this area.